Dragonfly Algorithm for Crowd NPC Movement Simulation in Metaverse - Santoso, Ong, Hansel; Junaedi, Hartarto; Santoso, Joan (Association for Scientific Computing Electrical and Engineering, 2022)
During The Pandemic Period The Development Of Virtual Reality (Vr) In The Field Of Social Media (Metaverse) Is Very Fast To Give New Experiences. To Provide A New Experience, The Development Of A Supporting Virtual World As A Gathering Place Is Needed, To Support The Presence Of Others That Become A Factor Of Social Virtual Presence (Svr) Npc Is Required. Npc Crowds Will Be Tested In Job Fair Case Study By Compared Dragonfly And Particle Swarm Optimization Algorithms. Algorithm Testing Will Be Adjustable With The Same Parameters And Profiles For Individuals And Objectives. After Experiment And Evaluation, Dragonfly Algorith Was More Optimal And Provided Better SVR.